If the graph of the equation \( y = \frac{2}{3}x \) is shifted 3 units up, you would add 3 to the equation.
So, the new equation would be:
\[ y = \frac{2}{3}x + 3 \]
Thus, the equation of the graph after the shift is \( y = \frac{2}{3}x + 3 \).
If the graph was shifted 3 units up, then the equation of the graph would be____________.
(1 point)
1 answer
If the graph of the equation \( y = \frac{2}{3}x \) is shifted 3 units up, you would add 3 to the equation.
So, the new equation would be:
\[ y = \frac{2}{3}x + 3 \]
Thus, the equation of the graph after the shift is \( y = \frac{2}{3}x + 3 \).